2017
DOI: 10.2147/tcrm.s123199
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Aldolase A predicts poor survival in patients with clear-cell renal cell carcinoma

Abstract: BackgroundAldolase A (ALDOA) is a glycolytic enzyme that drives the glycolytic metabolic pathway in mammalian cells. The overexpression of ALDOA was observed in a variety of cancers including clear-cell renal cell carcinoma (ccRCC). However, little was known about the clinicopathological significance and prognostic value of ALDOA in ccRCC patients.MethodsThe expression of ALDOA was detected using immunohistochemical staining in 162 formalin-fixed, paraffin-embedded ccRCC sections. Prognostic outcomes correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(42 reference statements)
4
12
0
Order By: Relevance
“…Aside from this, Na et al conducted multivariate analysis that revealed ALDOA as an independent and significant prognostic factor in clear cell renal cell carcinoma [18,19]. Herein we found that ALDOA was of much higher expression level in tumor tissues and cells than in normal tissues and cells.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 50%
“…Aside from this, Na et al conducted multivariate analysis that revealed ALDOA as an independent and significant prognostic factor in clear cell renal cell carcinoma [18,19]. Herein we found that ALDOA was of much higher expression level in tumor tissues and cells than in normal tissues and cells.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 50%
“…This again indicates a critical metabolic change, as previously observed in chRCC (27) and in gastric cancer (35). Conversely, an over-expression of gluconeogenic genes and proteins is frequently found in other tumor species, such as the over-expression of ALDOB in ccRCC (36) and colon cancer (37)(38)(39), which was also associated with tumor progression and poor prognosis.…”
Section: Discussionsupporting
confidence: 73%
“…Also the up-regulation of ALDOA has been reported in many cancer types, such as oral squamous cell carcinoma [40], hepatocellular carcinoma [41], and in RCC [42] and of ALDOA in ccRCC [43], osteosarcoma [44], and lung cancer [45]. Specifically, an increase in ALDOA was shown for all RCC types and was associated with metastasis, histological differentiation, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%